Factors affecting auditors' choice of advisors. - Choong, Michael. (2008)
Advisors play a vital role in developing the knowledge and skills of junior auditors and in improving the quality of audits. In this study, we focus on three variables that are likely to influence an auditor’s choice of advisor. The variables are the advisor’s educational qualification, the advisor’s level of audit experience and the deadline pressure faced by the auditor.